'Putting names with faces': a description of Epiactis handi sp. nov helps to resolve taxonomic confusion in species of the sea anemone Epiactis (Actiniaria, Actiniidae). (10th March 2015) - Larson, Paul G.; Daly, Marymegan
Abstract : We resolve taxonomic confusion regarding brooding sea anemones in the genus Epiactis Verrill 1869a in the North Pacific Ocean based on newly collected material from Hokkaido (Japan), Haida Gwaii (British Columbia, Canada), and Kodiak and Adak Islands (Alaska, USA), and museum specimens collected from the Kurile Islands (Russia), Alaska, British Columbia, Oregon (USA), and California (USA). We find that the internally brooding individuals identified by Hand & Dunn (1974) as Cnidopus ritteri (Torrey, 1902) and placed in the genus Epiactis by Fautin & Chia (1986) belong to a new species which we describe and name Epiactis handi sp. nov. Epiactis handi and E. ritteri can be differentiated by morphological and behavioural features including ornamentation and structure of the column and mode of brooding offspring. To highlight and clarify these differences, we redescribe E. ritteri based on specimens from Alaska. We provide the first account of external brooding in E. ritteri, which necessitates a clarification of the differences between E. ritteri and another externally brooding species from the North Pacific, E. japonica Verrill, 1869b. Epiactis ritteri and E. japonica differ in sex allocation, ornamentation of the column and details of external brooding: members of E. ritteri are gonochoric with a smooth column and brood groove which tightly closes, whereas those of E. japonica are hermaphroditic and have mid-column spherules.